СОЦИОЛИНГВИСТИЧЕСКИЙ ПОДХОД ПРИ ИНТЕРПРЕТАЦИИ РЕЧЕВОЙ ПРОДУКЦИИ ГОВОРЯЩЕГО (Filološke pripombe, 2019)
Article is constructed on the basis of two experiments. The first experiment describes influence of sociobiological factors of the person on the text created by him. In the second experiment the private model of sociolect is shown. Both experiments are aimed at the description of social experience of speaker, being shown at syntactic level of speech.